Supercritical carbon dioxide extraction of essential oils from Madhuca Longifolia flowers and its characterization - Achala Gupta; Mohammed A. Bareen; Priyanka Prasad; Anita Srivastava; Jatindra K. Sahu; Hariprasad P (Food Chemistry Advances)
Madhuca longifolia (mahua), a deciduous tree growing throughout the subtropical region of the India is a potential source of differentiated essential oils (EOs) with distinct bioactives. The study aimed to assess the effect of extraction methods on the quantitative and qualitative divergence in the chemical composition of flavor compounds of mahua flower EO. The advanced supercritical CO2 extraction (SCFE) and ultrasound-assisted solvent extraction (UAE) was compared to the conventional extraction techniques such as hydrodistillation (HD), enzyme-assisted hydrodistillation (HDE) and soxhlet (SOX) for their high-quality essential oil (EO) extraction efficiency. The maximum EO yield of 2.074% was obtained by SCFE followed by HD (1.64%). The presence of significant amount of terpenoids, including 2-acetyl-1-pyrroline, γ-terpinene, myrcene, α-terpineol, limonene, and L-linalool in EO was noticed with chemical profiling using GC-MS and E-Nose. SCFE method yielded EOs with best terpenoids as compared to other extraction methods. Furthermore, EO extracted using SCFE had higher total phenol and flavonoid content of 92.56mg GAE/g, 62.18mg QE/g respectively, and DPPH (100.06µg/mL), FRAP (91.52µM Fe(II)/g) antioxidant activity as compared to other extraction methods. A significantly (p<0.05) higher α-glucosidase and α-amylase inhibition of 37.16% and 43%, respectively, was shown by SCFE EOs. Total carotenoid content of EOs produced using all the extraction techniques ranged from 9.94 (HDE) to 29.673 (SCFE) mg/100g β-carotene. The “van krevelen” plots of CHNS analysis revealed ‘core metabolites’. This study illustrates that SCFE is a more effective method for EO extraction of high quality from low fat plant materials such as mahua flowers as compared to HD, HDE, SOX, and UAE.